The effects of sodium reduction on the gas phase of bread doughs using synchrotron X-ray microtomography. (April 2020) - Sun, Xinyang; Scanlon, Martin G.; Guillermic, Reine-Marie; Belev, George S.; Webb, M. Adam; Aritan, Serdar; Nickerson, Michael T.; Koksel, Filiz
Graphical abstract: Highlights: Link between dough bubbles and crumb cell of low sodium bread was explored. Bubble sizes in dough at the end of mixing are lognormally distributed. Low Na + limits bubble nucleation and promotes bubble growth in non-yeasted dough. Abstract: Globally, the bakery industry has a target of reducing sodium content in bread products. However, removing salt results in changes in the quality of bread through effects on dough's gas phase during the breadmaking process. Using synchrotron X-ray microtomography, the objective of this study was to investigate how sodium reduction induced changes in the gas phase parameters ( i.e., gas volume fraction, bubble size distribution (BSD) and its time evolution) of non-yeasted doughs made from a wide range of formulations ( i.e., wheat cultivar and water content) prepared with different mixing times. As salt content was reduced, a lower gas volume was retained in the dough by the end of mixing. Less gas bubbles were also retained if doughs were prepared from a stronger wheat cultivar, higher water content, and/or mixed for a shorter time. Rates of change in the median (R0 ) and the width (ε) of the fitted lognormal radius dependence of bubble volume fraction [BVF(R)] indicated that reduced sodium content permitted disproportionation to proceed more rapidly. Higher water content or longer mixing time also resulted in faster disproportionation, indicating that water content and mixing time can be manipulated as a means of increasing bubble stability against disproportionation during low-sodium breadmaking. An examination of relative changes in dough's gas phase parameters arising from sodium reduction demonstrated that wheat cultivar, water content and mixing time all affected dough's tolerance to sodium reduction. Therefore, attainment of good bread crumb cell structure in low-sodium bread formulas is a function of salt's effects on dough rheology in addition to its effect on yeast activity, so that dough formulation and mixing conditions also need to be considered.